PULSE OXIMETER USAGE IN PATIENT COVID-19 TREATMENT : AT A GLANCE - Ajrina, Amalia (Journal of Vocational Health Studies, 2021)
Background: The end of 2019, Wuhan experienced an insurgence of coronavirus within two months of this prolong pandemic. Patients with Covid-19 have chance in suffering a serious damage of respiratory system, which then lead to hypoxemia. The harmful of silent hypoxemia is that either the patients are remain untreated or they will not seek any treatment at all, though their blood oxygen levels (SpO2 levels) slowly decrease. Especially those who isolated at home. Pulse oximeter is a mini device that evaluate the level of arterial blood saturation. Purpose: This article gives a short review about the principle, application, advantage, and disadvantage of pulse oximetry in maintaining the Covid-19 patients with hypoxemia. Review: Two basic principles of pulse oximetry that are important: (a) to differentiate the oxyhemoglobin (HbO2 ) and deoxyhemoglobin (HHb), (b) to get the value of SpO2 from arterial compartment blood. How pulse oximeter detects SpO2 is based on the amount of red and IR light absorbed. Pulse oximeter can detect an abnormality of respiratory system in Covid-19 patients that may cannot be detected earlier. Pulse oximeter also helps diagnosing some severe pneumonia cases. It also can be realiable to diagnose an ARDS (Acute Respiratory Distress Syndroms) if the devices are found limited (WHO, 2020). Beside the advantages of pulse oximeter, there are some erroneous of readings. Conclusion: Pulse oximeter is a mini device which offers many advantages over its limitations. Limitation of pulse oximeter can be early detected and overcame with an introduction evaluation of clinical conditions of each patients.